Intra-operative and Immediate Post-operative Complications in a High Volume Cataract Surgery Center: Doi:10.36351/pjo.v36i4.1059 - Haider, Muhammad Ali; Sattar, Uzma; Amjad, Muhammad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the frequency of complications in a high volume phacoemulsification set up at a tertiary care eye hospital in Lahore. Study Design: Quasi experimental study. Place and Duration of Study: Al-Ehsan Eye Hospital, Lahore, from July 2017 to June 2019. Methods: Surgical outcomes of 6902 patients who had undergone phacoemulsification were included. Patients were excluded if they had ocular infections, lid margin diseases, adnexal diseases, those requiring a secondary anterior chamber surgery and those unfit for the procedure due to medical grounds. Every patient underwent a detailed history and complete clinical examination. All patients underwent the standard phacoemulsification technique and at the end of each surgery, subconjunctival injections of dexamethasone and gentamycin were given to the patients. Complications encountered during high volume cataract surgery were recorded and their percentages were calculated. Results: A total of 6902 patients underwent cataract surgery with 2.66% intra-operative and 6.94% immediate post-operative complications. The most common intra-operative complication was posterior capsular rupture (1.15%). In patients with capsular rupture the intra ocular lens was implanted within the sulcus in 61 cases (0.88%) while in 12 cases (0.17%) anterior chamber lens was implanted because of lack of capsular support. During the surgery intra ocular lens could not be implanted in 7 cases (0.10%) and they were left aphakic. The commonest immediate post-operative adverse outcome was corneal edema with striate keratopathy and decements folds in 197 cases (2.85%). Conclusion: High volume cataract surgery using appropriate techniques and sterilization does not compromise the quality of outcomes. Key Words: Cataract, Phacoemulsification, Vitreous loss.